(untitled) (Marketing Journal, 2026)
This article provides a scientific analysis of the key factors leading to distortions in the competitive environment, their impact on economic efficiency, and effective economic mechanisms for addressing these challenges. Based on international experience and data from the IMD World Competitiveness Ranking 2025, a comparative assessment of countries with high, medium, and low levels of competition № 1 -SON YANVA R, 202 6-YIL 160 is conducted. In addition, current reforms aimed at developing the competitive environment in Uzbekistan are evaluated, and scientific and practical conclusions and recommendations for improving market mechanisms are proposed.